Nitric oxide attenuated transforming growth factor-β induced myofibroblast differentiation of human keratocytes - Joo-Hee Park (Nature Portfolio, 2021)
Abstract Nitric oxide (NO) has the potential to modulate myofibroblast differentiation. In this study, we investigated the effect of exogenous NO on the myofibroblast differentiation of human keratocytes using sodium nitrite as a NO donor. Myofibroblasts were induced by exposing resting keratocytes to transforming growth factor (TGF)-β1. N-cadherin and α-smooth muscle actin (αSMA) were used as myofibroblast markers. Both resting keratocytes and -stimulated keratocytes were exposed to various concentrations of sodium nitrite (1 μM to 1000 mM) for 24 to 72 h. Exposure to sodium nitrite did not alter keratocytes’ viability up to a 10 mM concentration for 72 h. However, significant cytotoxicity was observed in higher concentrations of sodium nitrite (over 100 mM). The expression of αSMA and N-cadherin was significantly increased in keratocytes by TGF-β1 stimulation after 72 h incubation. The addition of sodium nitrite (1 mM) to TGF-β1-stimulated keratocytes significantly decreased αSMA and N cadherin expression. Smad3 phosphorylation decreased after sodium nitrite (1 mM) exposure in TGF-β1-stimulated keratocytes. The effect of NO was reversed when NO scavenger, 2-4-carboxyphenyl-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide (cPTIO) was added in the culture medium. Application of sodium nitrite resulted in significant decrease of corneal opacity when measured at 2 weeks after the chemical burn in the mouse. These results verified the potential therapeutic effect of NO to decrease myofibroblast differentiation of human keratocytes and corneal opacity after injury.